Studi Berbagai Metode Pembuatan BBM Dari Sampah Plastik Jenis LDPE dan PVC Dengan Metode Thermal & Catalytic Cracking (Ni-Cr/Zeolit) - (Arsitektur Universitas PGRI Semarang), Velma Nindita (Teknis, 2015)
Plastic is materials for packaging that is widely used today, because it has many advantages such as tough, light, and stable enough. However, the plastic used mostly in market are synthetic polymers which is made from crude oil and is difficult to decompose in nature, therefore, it can be increased environmental pollution, especially makes several waste in soil. One of many alternatives for recycling process is to convert waste plastics into fuel oil as for alternative energy source. This recycling process is referred to as tertiary recycling. Several studies aim to determine the characteristic of fuel oil from LDPE and PVC plastics that are applied to engine, so that can substitute a premium or diesel fuel used previously. Research methodology generally include two phases, namely the process of thermal (thermal cracking) and the addition of catalysts (catalytic cracking). The primary outcome of the studies are the optimal methods in fuel manufacture with raw materials LDPE and PVC plastic types with homogeneous catalysts based on modified natural zeolites with Ni and Cr for cracking waste plastics.Keywords: LDPE, PVC, Thermal, Catalytic, Cracking.